The cost analysis of implementing solar photovoltaic system for consumers in peninsular Malaysia based on current available schemes - Chong, Wei Hou (2020)
With introduction of Net Energy Metering (NEM) and Self-consumption (SELCO) scheme, consumer able to generate own electricity for own usage by promoting renewable energy while reduces the electricity bill. However, it is difficult to determine the benefits it can offered without having promising outcome restraining the public especially the household residential to participate the scheme. In this project, the cost analysis of both schemes integrated into the imitation energy load profile obtained from five sample household are studied. Energy load profile of the household residential are determined and simulation done by using PVSYST to study the effects of integration of NEM and SELCO scheme with photovoltaic system. Energy analysis was done to determine the overall energy consumption from the photovoltaic system and the energy required from the grid after implementing both NEM and SELCO scheme to maintain the household load. The result obtained is the reduction of energy consumption from the grid is highly reduced by using NEM scheme. Levelized cost of electricity (LCOE) is used to determine the cost of electricity after implementing NEM and SELCO schemes. The comparison of the levelized cost of electricity among the schemes with the residential tariff cost to determine the cost benefits of the introduced schemes. One of the results obtained is that the levelized cost of electricity for NEM and SELCO scheme able to achieve at RM 0.20 / kWh and RM 0.44 / kWh. Besides that, from the results obtained, the cost spends on the electricity on the 20th year able to achieve 27% to 51% savings for NEM implemented compare with non-PV user. The PV system with NEM have shorter payback period of 6.5 to 7.5 years with conditional requirement of minimum monthly energy consumption of 830 kWh onwards.